2000
DOI: 10.1139/f99-270
|View full text |Cite
|
Sign up to set email alerts
|

Size-dependent winter mortality of age-0 pikeperch (Stizostedion lucioperca) in Pärnu Bay, the Baltic Sea

Abstract: Winter mortality of pikeperch (Stizostedion lucioperca) at age 0 is dependent on size, based on samples collected with trawls during 1961-1994 in Pärnu Bay, Estonia. Mortality increased as mean length of pikeperch in the first autumn decreased. The size-dependent mortality was analysed as correlation between mean lengths at age 0 in autumn and changes in mean lengths between age 1 and age 0. When the varying lengths at age 0 were taken into account, the duration of winter also affected mortality; longer durati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
1
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 16 publications
1
30
1
1
Order By: Relevance
“…Contrary to our expectation, we did not find a direct relationship between the recapture rate and the stocking season in pikeperch. This is surprising because size-dependent winter mortality of juveniles is one of the key factors in year-class strength formation of pikeperch (Ruuhijärvi et al, 1996;Lappalainen et al, 2000) and closely related walleye Sander vitreus (Johnson et al, 1996), and is likely to be even more important in freshly stocked fish which need to spend extra energies for foraging appropriate habitat in unknown environment (Bolland et al, 2009;Buckmeier et al, 2005). Accordingly, several studies on different species concluded that fish stocked in spring and summer have better chance to survive, and thence to be recaptured, than those released just before the winter (Templeton, 1971;Strange and Kennedy, 1979;Kennedy et al, 1982;Vostradovsky, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to our expectation, we did not find a direct relationship between the recapture rate and the stocking season in pikeperch. This is surprising because size-dependent winter mortality of juveniles is one of the key factors in year-class strength formation of pikeperch (Ruuhijärvi et al, 1996;Lappalainen et al, 2000) and closely related walleye Sander vitreus (Johnson et al, 1996), and is likely to be even more important in freshly stocked fish which need to spend extra energies for foraging appropriate habitat in unknown environment (Bolland et al, 2009;Buckmeier et al, 2005). Accordingly, several studies on different species concluded that fish stocked in spring and summer have better chance to survive, and thence to be recaptured, than those released just before the winter (Templeton, 1971;Strange and Kennedy, 1979;Kennedy et al, 1982;Vostradovsky, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Year-class strength of the pikeperch is determined largely by the water temperature in May-June and by the abundance of sand goby (Pomatoschistus minutus) larvae (Erm 1976). The fish are characterised by size-dependent winter mortality at age 0, although longer durations of ice cover result in decreased size-dependent winter mortality (Lappalainen et al 2000).…”
Section: Plankton Communitiesmentioning
confidence: 99%
“…Thus, a significance level of 0.05 is required to allow a variable into the model, and a significance level of 0.05 is required for a variable to stay in the model. Two temperature thresholds of 0 or 10°C were analysed to select the best model, because for the juveniles, the threshold value of 10°C has been found to be important (Mooij et al 1994;Lappalainen et al 2000;Kjellman et al 2001), whereas the 0°C threshold was chosen to Year-class estimation…”
Section: Onset Of Growthmentioning
confidence: 99%